Keanekaragaman Jenis Pohon Di Hutan Pendidikan Konservasi Terpadu Tahura Wan Abdul Rachman - Agung Wahyudi; Sugeng Prayitno Harianto; Arief Darmawan (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Educational Forest is place for the public, especially students and researchers to study the interrelationship between the components of the forest ecosystem. Information on the types of trees is one of the basic information for education and the development and management of educational forest. This study is performed to fill a gap where information regarding biodiversity in Educational Forest of Tahura Wan Abdul Rahman is lacking. Sampling intensity used was 0.12% of the 1,143 ha forest area of education, so that is an area of 1.37 ha sample plots. Sample plot consisted of 10 plots in the sub-blok protected and 24 plots in sub-blok social forestry. It was found that 60 tree species were registered, which comprised of 41 species of trees scattered in the sub-blok protected and 19 species in sub-blok social forestry. Diversity Index in the sub-blok protected was 1.45 and is dominated by the kind of Kenari (Canarium commune) with 26.98% of Key Value Index. Diversity Index in the sub-blok social forestry was 1.09 and is dominated by Durian (Durio zibethinus) with 67.28% of Key Value Index. Keywords: tree diversity, forest biodiversity conservation education integrated, Tahura Wan Abdul Rachman